RESEARCH ON SOME FACTORS RELATED TO TIME OF GIVING OF GYNECOLOGISTS AT NGHE AN GENERAL HOSPITAL IN 2022 (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe clinical characteristics, labor time, some factors related to labor time andcomment on the effect of labor time on women giving birth at normal and full term at the Departmentof Obstetrics and Gynecology of General Hospital Nghe An in 2022.Research Methods: Analytical cross-sectional descriptive studyResults: A study of 295 women at the Department of Obstetrics and Gynecology, Nghe An Hospital,to investigate the clinical characteristics of the labor process and some factors related to the labortime of pregnant women. Information was collected by examination according to a pre-designedmedical record form. Results: Mean BMI was 25.47 ± 2.31. The most common first sign of labor isabdominal pain 44.1%; pink mucus or vaginal bleeding 33.5%. The average labor time of pregnantwomen with a baby is 19.32 ± 12.19 hours; of pregnant women at 11.90 ± 7.90 hours. The rate ofurinary retention was 13.5%; the rate of postpartum hemorrhage is 2.4%; the indication rate forartificial amniotomy was 73.2%. There is a weak positive correlation (r = 0.284, p30 had the longest stage 1a labor (p < 0.05).Conclusion: Prolonged labor is an increased length of labor compared with women with the samerisk factors. Labor for a long time can lead to serious complications or sequelae if not detectedearly and treated promptly. Complications may be: fetal distress in labor, threatened uterine rupture,uterine rupture, genitourinary fistula formation of the bladder or rectum, neonatal sepsis, postpartuminfection. Therefore, monitoring the labor process and detecting possible problems will limit thechanges that affect the health of the mother during labor
Keywords: Full-term pregnant women, prolonged labor.